The Impact of Tax Compliance, Earnings Quality, and Financial Performance on Future Earnings Response Coefficient: Evidence From Indonesia and Thailand - Tarmidi, Deden (Animo Repository, 2024)
This study was conducted to examine the impact of tax compliance and earnings quality, in addition to current financial performance, in predicting future earnings. Generally, future earnings are predicted using current earnings and their interactions with stock prices. The future earnings response coefficient is used by investors to measure it. Several previous studies have found different results on the effect of financial performance on future earnings, so further research is needed to develop any factors that affect future earnings. A total of 332 panel data were sourced from annual reports and historical stock prices from 83 manufacturing companies listed on the Indonesian Stock Exchange and the Thai Stock Exchange from 2014 to 2017. We use a quantitative approach with STATA 16 to analyze available data. The results indicate that earnings quality has a strong effect on future earnings, whereas tax compliance and financial performance are weak. These results have very important implications for entities that produce quality financial reports that help investors predict future earnings.